Chaturmukha-shivalinga - Temples of India Project Team (Jio Institute, 2024)
The four-faced linga, placed in the sanctum of the Harshnath Temple, is actively worshipped at the site. It has three benevolent faces, while the one facing north bears a fierce expression. They collectively represent the Sadashiva form of Shiva. The idol is contemporaneous to the main shrine but there is some debate over whether it was the original cult image in the shrine or a later replacement. Ambika Dhaka (2001:377) highlights a strong possibility of it being a later replacement based on two points. 1) According to the texts, the fierce face should be facing southward, but here it faces north. 2) There is a noticeable difference in the circumference of the linga in situ compared to the socket, with the latter being larger.